Motivasi Belajar dalam Perspektif Al-Qur'an - Sarnoto, Ahmad Zain; Abnisa, Almaydza Pratama (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Al-Quran motivates students to understand and observe their environment in learning, so the purpose of this study is to find and prove the concept of learning motivation according to the perspective of Al-Quran. The approach in this research is a descriptive-interpretative qualitative approach. The type of research used is library research. While the data obtained is a descriptive narrative of motivation in learning the Koran perspective. The Quranic perspective is related to the principles of learning motivation, including the principles: 1. The principles of learning motivation from within the learner or intrinsic include the principles of curiosity, asking, caring, confidence, relevance, and hope. 2. The principles from outside the learner or external, namely: the principle of fun, appreciation, self-actualization, and achievement.